2020
DOI: 10.1016/j.chom.2020.05.012
|View full text |Cite
|
Sign up to set email alerts
|

Sequential CRISPR-Based Screens Identify LITAF and CDIP1 as the Bacillus cereus Hemolysin BL Toxin Host Receptors

Abstract: Bacteria and their toxins are associated with significant human morbidity and mortality. While a few bacterial toxins are well characterized, the mechanism of action for most toxins has not been elucidated, thereby limiting therapeutic advances. One such example is the highly potent pore-forming toxin, hemolysin BL (HBL), produced by the gram-positive pathogen Bacillus cereus. However, how HBL exerts its effects and whether it requires any host factors is unknown. Here, we describe an unbiased genome-wide CRIS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
21
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 51 publications
2
21
1
Order By: Relevance
“…Several studies proved that the B. cereus enterotoxins affect a variety of different target tissues and cell lines, such as rabbit retinal tissue and ileum [ 303 ], sheep blood [ 300 ], as well as Vero (African green monkey kidney), CHO (Chinese hamster ovary), HUVEC (human umbilical vein/vascular primary endothelial cells), Hep-2 (human cervix), CaCo-2 (human colon), Hep-G2 (human liver), A549 (human lung), RPMI 8226 (human B lymphocyte), A204 (human muscle), Jurkat (human T lymphocyte), U937 (human monocyte), HT-29 (human colon), IPEC-J2 (swine colon), BMDM (primary bone marrow derived macrophages), EC (mouse lung primary endothelial), RAW 264.7 (murine macrophages), B16-BL6 (murine skin), B16-F10 (murine skin), and HT-1080 (human connective tissue) cells [ 204 , 227 , 306 , 335 , 337 , 338 ]. At this point, the question frequently arose whether specific target structures and receptors for Hbl and Nhe exist.…”
Section: The Diarrheal Enterotoxinsmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies proved that the B. cereus enterotoxins affect a variety of different target tissues and cell lines, such as rabbit retinal tissue and ileum [ 303 ], sheep blood [ 300 ], as well as Vero (African green monkey kidney), CHO (Chinese hamster ovary), HUVEC (human umbilical vein/vascular primary endothelial cells), Hep-2 (human cervix), CaCo-2 (human colon), Hep-G2 (human liver), A549 (human lung), RPMI 8226 (human B lymphocyte), A204 (human muscle), Jurkat (human T lymphocyte), U937 (human monocyte), HT-29 (human colon), IPEC-J2 (swine colon), BMDM (primary bone marrow derived macrophages), EC (mouse lung primary endothelial), RAW 264.7 (murine macrophages), B16-BL6 (murine skin), B16-F10 (murine skin), and HT-1080 (human connective tissue) cells [ 204 , 227 , 306 , 335 , 337 , 338 ]. At this point, the question frequently arose whether specific target structures and receptors for Hbl and Nhe exist.…”
Section: The Diarrheal Enterotoxinsmentioning
confidence: 99%
“…Moreover, its related protein CDIP1 was found to be an alternative Hbl receptor in the absence of LITAF. LITAF/CDIP1 double knockout cells were completely resistant towards Hbl B binding as well as Hbl toxicity, and LITAF knockout mice were resistant towards Hbl toxicity [ 335 ]. Nevertheless, the specific Nhe receptor, which is more than likely to exist, is still unidentified.…”
Section: The Diarrheal Enterotoxinsmentioning
confidence: 99%
“…Next to the enterotoxins, which contribute to the largest part of the disease, further (putative) virulence factors such as enterotoxin FM, hemolysins II and III, cereolysin O, phospholipase C, the metalloproteases InhA1 and NprA, further exoproteases, or sphingomyelinase might be involved [289,[399][400][401][402][403][404][405][406][407]. It has been shown that the B. cereus enterotoxins affect target cells of a great variety of different tissue, origin and species [388,391,[408][409][410][411][412][413]. Furthermore, they form pores on planar lipid bilayers [393,414,415], which favored the assumption of rather unspecific cell binding for several years.…”
Section: Production Of Diarrheal Enterotoxinsmentioning
confidence: 99%
“…Furthermore, they form pores on planar lipid bilayers [393,414,415], which favored the assumption of rather unspecific cell binding for several years. Nevertheless, just recently, LPS-induced TNF-α factor (LITAF) was determined as the main and its related protein CDIP1 as alternative receptor for Hbl, while a specific binding site for Nhe has still not been discovered [410]. The fate of the affected target cells has also been described as pore formation in the membranes (measured via influx of propidium iodide into the cells) [378,388], cell survival or death (measured via LDH or alkaline phosphatase release and bioassays targeting the respiratory chain) [359,374,409,416], or programmed cell death via apoptotic or inflammatory pathways [408,412,417].…”
Section: Production Of Diarrheal Enterotoxinsmentioning
confidence: 99%
“…In terms of Hbl, the ratio at L2: L1: B = 1:1:10/ 10:1:10 prompts the most rapid pore formation [ 20 ]. Recent studies also found that LITAF and CDIP1 work as the Hbl receptor [ 31 ]. The signaling pathways triggered by Nhe, as shown in Figure 1 a, include the induced cell apoptosis though ASK1 and Fas-p38 MAPK mediated caspase-8 dependent pathways [ 32 ].…”
Section: Introductionmentioning
confidence: 99%